The hope as social commitment in the processing of tacrolimus - Alessandra Suzin Bertan; Marco Aurélio Cremasco (The Journal of Engineering and Exact Sciences)
The 2020 year shows the fragility of the human been due to a virus that affects the people dependent of immunosuppressant agents. The aim of this paper it to contextualize the importance of the hope as essential element in chemical design to obtain tacrolimus, and to professionals involved in this research. It is presented the processing of this drug and the impact of their results on scientific and technological products, as well as in the human resource formation in the undergraduate and graduate levels, and impact in the society, showing that university extension can be done with external public, beyond of its technical production, bringing social hope to people who remain invisible to public policies.